2003
DOI: 10.1373/49.5.727
|View full text |Cite
|
Sign up to set email alerts
|

The Concentration of Circulating Corticotropin-releasing Hormone mRNA in Maternal Plasma Is Increased in Preeclampsia

Abstract: Background: Increased fetal DNA in maternal plasma/ serum has been reported in pregnancies complicated by preeclampsia. We hypothesize that fetal RNA may also be increased in maternal plasma in preeclampsia. Methods: We developed a real-time quantitative reverse transcription-PCR assay to measure the concentration of the mRNA of the corticotropin-releasing hormone (CRH) locus. Peripheral blood samples were obtained from healthy pregnant women both before and 2 h after delivery. Peripheral blood samples were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(99 citation statements)
references
References 33 publications
6
86
1
4
Order By: Relevance
“…The increased release of ADAM12 mRNA into the plasma of IUGR with PET pregnant women may be related to increased placental ADAM12 mRNA expression in preeclamptic placental tissue, which is in agreement with previous studies on ADAM12 at the protein level (Gack et al, 2005). Moreover, increased concentrations of cellfree nucleic acids in PET has been reported in several studies (Lo et al, 1999;Zhong et al, 2001;Ng et al, 2003a;Purwosunu et al, 2007) and speculated to be associated with increased placental apoptosis in pregnancies complicated by PET .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The increased release of ADAM12 mRNA into the plasma of IUGR with PET pregnant women may be related to increased placental ADAM12 mRNA expression in preeclamptic placental tissue, which is in agreement with previous studies on ADAM12 at the protein level (Gack et al, 2005). Moreover, increased concentrations of cellfree nucleic acids in PET has been reported in several studies (Lo et al, 1999;Zhong et al, 2001;Ng et al, 2003a;Purwosunu et al, 2007) and speculated to be associated with increased placental apoptosis in pregnancies complicated by PET .…”
Section: Discussionsupporting
confidence: 89%
“…Quantification of plasma placental RNA is not limited by the fetal gender or genotype, and allows marker development from disease-specific gene expression patterns. For example, our group has reported that circulating fetal RNA analysis could be applied for the noninvasive prenatal diagnosis of pre-eclampsia (PET) and fetal aneuploidies (Ng et al, 2003a;Ng et al, 2004;.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the placenta is the major source of circulating cell-free fetal nucleic acids in maternal plasma (5)(6)(7). Significantly elevated levels of total cell-free DNA and selected placenta-specific RNA transcripts have also been reported in the maternal plasma of women with PE (8)(9)(10)(11), restricted fetal growth (12), and preterm birth (13)(14)(15), supporting a role for cell-free nucleic acids as a noninvasive tool for placental monitoring. Previous studies have attempted to provide a comprehensive assessment of maternal plasma nucleic acids by microarray analysis, massively parallel transcriptomic, or methylomic sequencing (16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 97%
“…Another advantage is the fact that fetal DNA can be discovered in maternal blood as early as the fourth week of gestation, and reliably after the seventh week of gestation [54]. In addition to fetal DNA, fetal mRNA and microRNAs also exist in maternal plasma, and they can provide knowledge about fetal gene expression, mirroring different physiological conditions [48,[55][56][57].…”
Section: Cell-free Fetal Dna and Mrna In Maternal Bloodmentioning
confidence: 99%